Análisis de la aplicación de la pena privativa de libertad en los consumidores de sustancias estupefacientes o psicotrópicas, que superan las cantidades permitidas, de las sentencias apeladas ante la Corte Provincial de Pichincha, en el año 2018 - Chiluiza Naranjo, Elva Elizabeth (2020)
The present article has as object of study to drug use and implications in the legal field, so that has been resorted to references contained in national and international regulations; the threshold table established by the ex-Consep was analyzed, to understand how the parameters related to maximum quantities allowed for consumption and traffic scales have served to determine a penalty; also, the reference was made to the legal assets involved, as well as violated rights of drug users when establishing a custodial sentence. An analysis was made of the sentences put to knowledge of the la Sala Penal de la Corte Provincial de Pichincha, in that they exceed the maximum allowed of the substance for consumption, the legal foundations of the judges to implant a custodial sentence or ratification of the state of innocence for drug users have been analyzed, this study aims to contribute in offering an overview of the legal reality and the criteria used in these cases.